Building up autonomy through reading strategies (2014)
This article reports on an action research project conducted with six ninth grade students in a rural public school in Colombia. The purpose of the study was to determine how the implementation of three reading strategies (skimming, scanning, and making predictions), when reading topics selected by learners, helps them to improve their reading comprehension and promotes their autonomy in the learning process. The results show that these learners developed some autonomous features such as making decisions for learning and doing assigned homework, increasing reading awareness and motivation. Additionally, the training on reading strategies allowed them to succeed in their reading comprehension. We conclude that these reading strategies are tools that take learners along the path of autonomy.En este artículo se reportan los resultados de un proyecto de investigación-acción llevado a cabo con seis estudiantes de noveno grado en un colegio público rural. El propósito fue determinar el impacto de tres estrategias de lectura en inglés (identificar información específica, entender la idea principal y hacer predicciones) en la promoción de la autonomía y la compresión lectora. Los resultados evidenciaron que los estudiantes adquirieron algunos rasgos de autonomía, tales como tomar decisiones para aprender y hacer sus tareas asignadas, ser más conscientes de su proceso de lectura y estar más motivados para el aprendizaje. Así mismo, la capacitación referente a las estrategias de lectura les permitió mejorar su comprensión lectora. Se puede concluir que estas estrategias son herramientas que le sirven al estudiante para su formación en autonomía.